2014
DOI: 10.4081/jear.2014.715
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Mentha piperita L. and Mentha pulegium L. essential oils on nutritional indices of Plodia interpunctella Hübner (Lepidoptera: Pyralidae)

Abstract: Antifeedant activity of plant extracts from Mentha piperita L. and Mentha pulegium L. were tested against the Indian meal moth, Plodia interpunctella (Hübner). The nutritional indices: relative growth rate (RGR), relative consumption rate (RCR), efficiency of conversion of ingested food (ECI) and feeding deterrence index (FDI) were measured for first-instar larvae (15-d old). Treatments were evaluated using a flour disk bioassay in the dark, at 25±1°C and 60±5% R.H. Concentrations of 0, 0.1, 0.5, 0.75, 1, 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…Effects of different essential oils on nutritional indices of stored product insects have been studied by different researchers (Huang et al, 2002;Huang and Ho, 1998;Huang et al, 2002;Negahban and Moharamipour, 2007;Saeidi and Hassanpour, 2014). According to our findings nutritional indices (RGR, RCR and ECI) of R. dominica adults decreased with increasing concentration level of EOs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Effects of different essential oils on nutritional indices of stored product insects have been studied by different researchers (Huang et al, 2002;Huang and Ho, 1998;Huang et al, 2002;Negahban and Moharamipour, 2007;Saeidi and Hassanpour, 2014). According to our findings nutritional indices (RGR, RCR and ECI) of R. dominica adults decreased with increasing concentration level of EOs.…”
Section: Discussionsupporting
confidence: 55%
“…While, for T. castaneum, concentrations of 35 and 99 mg/g food is required to reduce the growth rate (RGR) and RCR, respectively. Saeidi and Hassanpour (2014) reported that M. piperita essential oil was more effective than M. pulegium by significantly reducing P. interpunctella nutritional indices. Therefore, most of the essential oils have antifeedant activity and their potential on nutritional indices should be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of this pest in storage systems mainly depends on fumigants such as methyl bro- mide or phosphine, and fogging with pyrethrins or dichlorvos. However, methyl bromide has been banned in many countries since 2004 because of its ozone depleting properties (Hansen & Jensen, 2002;Saeidi & Yousefi, 2013;Saeidi & Hassanpour, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Annually, million tons of strategic stored products such as cereals, nuts, grains and processed foods are ruined in developing countries, making existing economic problems more complex (Rharrabe et al, 2007;Amorim et al, 2008;Saeidi & Hassanpour, 2014). Among more than 500 beetle and moth pest species (Rajendran, 2002), the Indianmeal moth (IMM) Plodia interpunctella (Hübner) is the most detrimental pest, and causes a major part of the damage to stored food (Mohandass et al, 2007).…”
Section: Introductionmentioning
confidence: 99%